Protein- and Cell-Resistance of Zwitterionic Peptide-Based Self-Assembled Monolayers: Anti-Biofouling Tests and Surface Force Analysis - Chang, Ryongsok; Quimada Mondarte, Evan Angelo; Palai, Debabrata; Sekine, Taito; Kashiwazaki, Aki; Murakami, Daiki; Tanaka, Masaru; Hayashi, Tomohiro (Frontiers in Chemistry, 2021)
Peptide-based self-assembled monolayers (peptide-SAMs) with specific zwitterionic amino acid sequences express an anti-biofouling property. In this work, we performed protein adsorption and cell adhesion tests using peptide-SAMs with repeating units of various zwitterionic pairs of amino acids (EK, DK, ER, and DR). The SAMs with the repeating units of EK and DK (EK and DK SAMs) manifested excellent bioinertness, whereas the SAMs with the repeating units of ER and DR (ER and DR SAMs) adhered proteins and cells. We also performed surface force measurements using atomic force microscopy to elucidate the mechanism underlying the difference in the anti-biofouling property. Our measurements revealed that water-induced repulsion with a range of about 8 nm acts between EK SAMs (immobilized on both probe and substrate) and DK SAMs, whereas such repulsion was not observed for ER and DR SAMs. The strength of the repulsion exhibited a clear correlation with the protein- and cell-resistance of the SAMs, indicating that the interfacial water in the vicinity of EK and DK SAMs is considered as a physical barrier to deter protein and cells from their adsorption or adhesion. The range of the repulsion observed for EK and DK SAMs is longer than 8 nm, indicating that the hydrogen bonding state of the interfacial water with a thickness of 4 nm is modified by EK and DK SAMs, resulting in the expression of the anti-biofouling property.